2014
DOI: 10.7717/peerj.324
|View full text |Cite
|
Sign up to set email alerts
|

The Adult ADHD Self-Report Scale (ASRS): utility in college students with attention-deficit/hyperactivity disorder

Abstract: Background. The number of students with Attention Deficit/Hyperactivity Disorder (ADHD) enrolled in colleges and universities has increased markedly over the past few decades, giving rise to questions about how best to document symptoms and impairment in the post-secondary setting. The aim of the present study was to investigate the utility and psychometric properties of a widely-used rating scale for adults with ADHD, the Adult ADHD Self-Report Scale (ASRS-V1.1), in a sample of post-secondary students with AD… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 34 publications
(45 reference statements)
3
55
1
4
Order By: Relevance
“…Thus, participants comprising our sample were likely to be higher-functioning and psychologically healthier than we would expect from clinical samples comprised of individuals with ADHD. This interpretation is supported by the fact that total ADHD symptom scores in our sample were lower than what has been reported from samples of individuals diagnosed with ADHD (see Gray et al 2014).…”
Section: Limitations Future Directions and Conclusioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Thus, participants comprising our sample were likely to be higher-functioning and psychologically healthier than we would expect from clinical samples comprised of individuals with ADHD. This interpretation is supported by the fact that total ADHD symptom scores in our sample were lower than what has been reported from samples of individuals diagnosed with ADHD (see Gray et al 2014).…”
Section: Limitations Future Directions and Conclusioncontrasting
confidence: 69%
“…The mean total score on the ASRS (i.e., summed across all 18 items) in our sample was 26.50 (SD=12.53), which is a much lower mean than has been reported on this measure in samples of individuals diagnosed with ADHD (see Gray et al 2014;M=49.1, SD=9.2). Participants in our sample who reported that they were taking stimulants to treat a mental illness (3.7 %, n=11) had a higher mean ASRS score (M=39.27, SD=6.29) than that for our overall sample; however, this mean score still is noticeably lower than that reported by Gray et al (2014).…”
Section: Preliminary Results and Overviewmentioning
confidence: 77%
“…Although, it has been suggested that multimodal assessment, including informant and selfreport, should be used to gather more information about symptoms of ADHD (Alexander and Liljequist, 2013), self-report measures are frequently used to confirm ADHD symptomatology in university students (Gray et al, 2014). While research on assessment with this specific population is limited, in a study conducted by Katz et al (2009), participants self-reported higher childhood and current symptoms scores than informants.…”
Section: Adult Adhd Self-report Scales (Asrs-v11)mentioning
confidence: 94%
“…Similarly, IQ can potentially affect ASRS scores (Gray et al, 2014). However, we attempted to estimate the potential effect of intelligence by using information about the participants' education level, which can be used to estimate IQ (Rammstedt, & Rammsayer, 2002).…”
Section: Limitationsmentioning
confidence: 99%